The Biochemical Role of Zinc, Copper, and Iron in Carcinogenesis / Review - Hala Sabry Al-Atbi; Zainab Kadhim Al-Khazragie; Karrar Hassan Thamir (Academia Open, 2026)
General Background: Trace elements are essential micronutrients that regulate enzymatic activity, cellular metabolism, and redox balance in biological systems. Specific Background: Among these elements, zinc, copper, and iron participate in processes closely associated with tumor development, including oxidative stress regulation, DNA repair, angiogenesis, and cell proliferation. Knowledge Gap: Although numerous studies describe the biological roles of individual trace elements, limited research has examined their combined molecular interactions and integrated contribution to cancer progression. Aims: This review analyzes the roles of zinc, copper, and iron in carcinogenesis by examining their involvement in oxidative stress generation, genomic instability, angiogenic signaling, and cellular growth mechanisms, while also discussing potential diagnostic and therapeutic applications related to trace-element modulation. Results: Evidence indicates that zinc supports antioxidant defense and DNA repair mechanisms, while dysregulated copper promotes angiogenesis and tumor cell migration. Iron participates in redox reactions that generate reactive oxygen species capable of inducing oxidative DNA damage and genomic instability. Alterations in the concentration and bioavailability of these elements are associated with tumor development and progression across multiple cancer types. Novelty: This study presents an integrated perspective on the collective biochemical roles of zinc, copper, and iron in carcinogenesis, emphasizing their interconnected molecular mechanisms rather than isolated biological functions. Implications: Understanding the coordinated behavior of these trace elements provides new directions for biomarker development, early detection strategies, and therapeutic approaches based on regulating metal homeostasis in cancer biology. Highlights: Metal Imbalance Contributes to Oxidative Stress, Genomic Instability, and Abnormal Cellular Proliferation in Tumor Development. Angiogenic Signaling and Tumor Migration Are Associated With Elevated Copper Concentrations in Malignant Tissues. Redox Reactions Involving Iron Generate Reactive Oxygen Species That Damage Genetic Material and Promote Genomic Instability. Keywords: Trace Elements, Zinc, Copper, Iron, Carcinogenesis